Aspects of termination of administrative contracts (Revista do Tribunal Regional Federal da 3ª Região, 2015)
Cultivators of the science of Administrative Law and, in general, administrators and civil servants of the Administration, have focused on the study of the termination of administrative contracts, because it is not uncommon, as one would wish, for there to be disrespect for the rules contained in laws, administrative acts and contractual instruments signed between the Public Authority and the private individual. Thus, the unfortunately constant non-compliance with the precepts relating to the fulfillment of contractual and legal obligations leads to the need for a careful analysis of the legal-normative framework, specifically with regard to the consequences of the violation of a legal duty. For this reason, there is an abundance of dissent and opinions of the most varied shades, usually aimed at solving specific cases, i.e., aimed at “administrative practice”. Therefore, texts on administrative contracts contain - inarguably - an idea, perhaps aspects that have not been addressed, seen or even systematized. In short, there is always a broad spectrum to be analyzed on the subject. Hence the importance of these excerpts; they are a systematic approach to “some aspects” of contractual termination. Of course, this simple study is not intended to exhaust the subject. Absolutely; it is intended that the reader can reflect on it, drawing their own conclusions.
Keywords: administrative contracts; legal regime; execution; rescission